Crisis Communication Strategy Of Pt. Pelabuhan Indonesia II (PERSERO) Branch Of Bengkulu During The Covid-19 Pandemic (study on land dispute cases) - Intania Pitaloka; Sapta Sari; Indria Indria (Jurnal ISO: Jurnal Ilmu Sosial, Politik dan Humaniora, 2023)
This study aims to determine the Crisis Communication Strategy carried out by PT. Pelabuhan Indonesia II (Persero) Branch of Bengkulu related to land disputes with the community. This research is a qualitative descriptive research that uses data collection by means of interviews, observation and documentation. According to the theory put forward (Kriyantono, 2015), the results of the study show that several steps in the crisis communication strategy of PT Pelabuhan Indonesia II (Persero) Branch of Bengkulu have been implemented well, namely having internal and external communication teams to resolve problems, confirm and contact PWI ((Indonesian Journalists Association) regarding media that reporting negative information, providing facts to the public in the form of land ownership rights, holding press conferences and answering questions from the mass media while still implementing health protocols in the midst of the covid-19 pandemic, maintaining reputational communication by holding activities, having a one-way communication system, namely coordination between the legal and internal control divisions as well as the public relations and customer service divisions, maintaining empathetic communication by always using a polite style of language and without mentioning the real names of the persons concerned, does not cover up information within the company related to the problems that occur, is also careful in conveying information to the public in order to maintain the good name of the company, and opens communication channels to the public using mass media, websites and call centers available in the company.